PELAKSANAAN ZAKAT PERTANIAN KAKAO DALAM PERSPEKTIF HUKUM ISLAM: (STUDI KASUS DI DESA MAJA KECAMATAN MARGA PUNDUH KABUPATEN PESAWARAN PROVINSI LAMPUNG) - Saefudin, Akhmad; Iswandi, Irvan; Aminulloh, Ali (Journal of Islamic Studies, 2023)
Zakat is part of the assets that must be issued by Muslims. Results from agriculture that have economic value must also be issued zakat. Agricultural zakat is zakat maal or wealth zakat resulting from agriculture or plantations that has economic value, and is usually used for human consumption. The amount of zakat is regulated in the book of Islamic jurisprudence. Most of the residents of Maja Village work as farmers, especially cocoa producers.The author is motivated by curiosity about how the implementation of agricultural zakat in Maja Village. In accordance with the research objective, namely to determine the implementation of agricultural zakat in Maja Village, Marga Punduh District, Pesawaran Regency, Lampung Province. This study will also examine whether the implementation of agricultural zakat in Maja Village is in accordance with Islamic law and what factors influence its implementation. This research used descriptive qualitative with the type of field research (field research). The data collection process in this study used interview, observation, and documentation techniques. The results of the study show that the implementation of agricultural zakat in Maja Village is only 2.5% of the yield and this shows that the implementation of agricultural zakat in Maja Village does not meet the criteria of Islamic law. This is influenced by several factors, including the lack of knowledge about agricultural zakat, habitual factors, and the lack of education regarding agricultural zakat in Maja Village.